Systematic assessment of salt tolerance based on morpho-physiological traits and genes related in inbred rice lines at the seedling stage - RENY HERAWATI; MARULAK SIMARMATA; MASDAR MASDAR; BAMBANG S. PURWOKO; MISWATI MISWATI (Society for Indonesian Biodiversity, 2024)
Abstract. Herawati R, Simarmata M, Masdar, Purwoko BS, Miswati. 2023. Systematic assessment of salt tolerance based on morpho-physiological traits and genes related in inbred rice lines at the seedling stage. Biodiversitas 24: 6256-6267. Salinity stress is an abiotic constraint that limits rice productivity. Salinity-tolerant traits are very complex and involve many genes. Therefore, it is difficult to conclude how rice plants respond to salinity stress. This study aimed to investigate the genetic potential of 19 rice genotypes for salt tolerance as well as the quantitative impacts of varying salinity stress levels on a subset of the genotypes. Salinity tolerance is identified in two stages: assessing salinity stress in nutrient solutions using 0, 5,000 (EC 7.8 dS.m-1), and 10,000 ppm (EC 15.62 dS.m-1). Gene expression analysis detected genes controlling salinity stress tolerance using two pairs of specific primers: DST (Drought Salt Tolerance) and OsAPX (ascorbate peroxidase). The results showed that all lines could survive high salinity stress up to EC 7.8 dS.m-1. Biplot is reflected in K-means grouping the 21 rice genotypes into three major groups, namely salt-sensitive (1 genotype, 4.75%), moderately salt-tolerant (2 genotypes, 9.5%), and salt-tolerant-very tolerant (18 genotypes, 85.7%). The DST and OsAPX1 genes showed both genes were expressed under salinity stress, although some lines showed smears or even did not appear at all, namely in G3 and G7. This result is consistent with the PCA analysis, where genotypes G3 and G7 are categorized as moderately tolerant. This study reveals that screening at the seedling stage combined with marker-assisted selection can identify tolerant genotypes. Furthermore, conducting field trials on soil salinity with EC > 4 dS.m-1 is recommended to obtain salinity-tolerant lines as potential new varieties.